Contract contingencies and uncertainty: Evidence from product market contracts - Hui, Kai Wai; Oh, Jun; She, Guoman; Yeung, P. Eric (Journal of Accounting and Economics, 2025)
We study contingencies written in firms' material product market contracts, focusing on the theoretical prediction of uncertainty as an important determinant. We identify contract contingencies from firms’ public regulatory filings and examine the effects of general business uncertainty and specific innovation-related uncertainty. To enhance causal inference, we utilize two major business shocks (i.e., the 2008 Financial Crisis and the COVID pandemic) and the diffusion of 29 disruptive innovation shocks (Bloom et al., 2021). We also explore the effects of re-negotiation costs and writing costs. Overall, our empirical results are consistent with predictions from dynamic models of incomplete contracting.